Indonesia's Public Satisfaction Soars Despite Service Quality Shortcomings: Kepuasan Masyarakat Indonesia Melonjak Meski Ada Kekurangan dalam Kualitas Layanan - mochamad mansur nur hidayat; Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the quality of population administration services in Bangsal District, focusing on public satisfaction and aspects such as physical facilities, reliability, responsiveness, assurance, and empathy. Using a qualitative approach with interviews, observations, and documentation, the findings reveal that, despite inadequate physical facilities and reliability issues, public satisfaction is relatively high due to effective communication and improved security measures. However, staff responsiveness and empathy need improvement, with key challenges including limited staff and infrastructure. The study suggests enhancements in physical infrastructure and staff training to further improve service quality, offering insights for policy changes and resource allocation. Highlight: Public Satisfaction: High due to effective communication and improved security. Physical Facilities: Inadequate infrastructure impacts service quality. Staff Responsiveness: Needs improvement through better training and support. Keyword: Population administration, service quality, public satisfaction, Bangsal District, qualitative research